Find the general solution of the differential equation
(D^2+1)y=x^3+e^xcosx
"\\left( {{D^2} + 1} \\right)y = y'' + y = {x^3} + {e^x}\\cos x"
Сharacteristic equation:
"{k^2} + 1 = 0"
"{k^2} = - 1"
"k = \\pm i"
Then the general solution of the homogeneous equation is
"{y_0} = {C_1}\\cos x + {C_2}\\sin x"
We will seek a particular solution in the form
"\\widetilde y = A{x^3} + B{x^2} + Cx + D + {e^x}\\left( {E\\cos x + F\\sin x} \\right) \\Rightarrow"
"\\Rightarrow {\\widetilde y^\\prime } = 3A{x^2} + 2Bx + C + {e^x}\\left( {E\\cos x + F\\sin x} \\right) + {e^x}\\left( { - E\\sin x + F\\cos x} \\right) \\Rightarrow"
"\\Rightarrow {\\widetilde y^{\\prime \\prime }} = 6Ax + 2B + {e^x}\\left( {E\\cos x + F\\sin x} \\right) + {e^x}\\left( { - E\\sin x + F\\cos x} \\right) + {e^x}\\left( { - E\\sin x + F\\cos x} \\right) + {e^x}\\left( { - E\\cos x - F\\sin x} \\right)"
Substitute the obtained values into the original equation:
"6Ax + 2B + {e^x}\\left( {E\\cos x + F\\sin x} \\right) + {e^x}\\left( { - E\\sin x + F\\cos x} \\right) + {e^x}\\left( { - E\\sin x + F\\cos x} \\right) + {e^x}\\left( { - E\\cos x - F\\sin x} \\right) + A{x^3} + B{x^2} + Cx + D + {e^x}\\left( {E\\cos x + F\\sin x} \\right) = {x^3} + {e^x}\\cos x"
"A{x^3} + B{x^2} + x\\left( {6A + C} \\right) + D + 2B + {e^x}\\cos x(E + F + F - E + E) + {e^x}\\sin x(F - E - E - F + F) = {x^3} + {e^x}\\cos x"
"\\left\\{ \\begin{matrix}\nA = 1\\\\\nB = 0\\\\\n6A + C = 0\\\\\nD + 2B = 0\\\\\n2F + E = 1\\\\\n - 2E + F = 0\n\\end{matrix} \\right. \\Rightarrow A = 1,\\,B = 0,\\,C = - 6,\\,D = 0,\\,F = \\frac{2}{5},\\,E = \\frac{1}{5}"
So,
"\\widetilde y = {x^3} - 6x + {e^x}\\left( {\\frac{1}{5}\\cos x + \\frac{2}{5}\\sin x} \\right)"
"y = {y_0} + \\widetilde y = {C_1}\\cos x + {C_2}\\sin x + {x^3} - 6x + {e^x}\\left( {\\frac{1}{5}\\cos x + \\frac{2}{5}\\sin x} \\right)"
Answer: "y = {C_1}\\cos x + {C_2}\\sin x + {x^3} - 6x + {e^x}\\left( {\\frac{1}{5}\\cos x + \\frac{2}{5}\\sin x} \\right)"
Comments
Leave a comment